Demonstratie 'Vrede in Vietnam' voor het ministerie van Buitenlandse Zaken. Serie van 6 foto's - Wöhlken, Hans,
Demonstratie 'Vrede in Vietnam' voor het ministerie van Buitenlandse Zaken. Serie van 6 foto's.